High Altitude Platform Stations (HAPS) : The new Frontier at the intersection between Air and Space Law - Hobe, Stephan (University of Pretoria, 2024)
Dissertation (LLM (International Air, Space & Telecommunications Law))--University of Pretoria, 2023.